Κ-Carrageenan hexamer have significant anti-inflammatory activity and protect RAW264.7 Macrophages by inhibiting CD14. (June 2019) - Guo, Juanjuan; Han, Su; Lu, Xu; Guo, Zebin; Zeng, Shaoxiao; Zheng, Xiuhua; Zheng, Baodong
Graphical abstract: Highlights: Anti-inflammatory activity of purified κ-carrageenan hexamer (KCH) was investigated. The intercellular proteomic responses and CD14/REL-dependent NF-κB pathway were demonstrated. The receptor protein (CD14) of KCH recognizing RAW 264.7 macrophages were identified. The binding sites of KCH to CD14 were found that KCH recognized as regions to inhibit LPS binding. Abstract: κ-Carrageenan hexamer (KCH, α-DA-1 → 3-β-G4S-1 → 4-α-DA-1 → 3-β-G4S-1 → 4-α-DA-1 → 3-G4Srα/β) are negatively charged sulfated oligosaccharides that demonstrate broad-spectrum immunoregulatory activities. However, the functional mechanism and interaction sites of KCH with recognition proteins have not been elucidated. The study aimed to investigate the anti-inflammatory signaling pathways and expound the mechanism of KCH competing with LPS in LPS-induced RAW264.7 macrophages. Expression of cytokines (NO, TNF-α, IL-β, IL-8), genes (mTNF-α, mIL-β, mIL-8) and proteins (iNOS, COX-2) involved in inflammation were significantly suppressed ( p  < 0.05) with KCH pre-treatment. Proteomics profiling demonstrated that the CD14/REL-dependent NF-κB inflammatory pathway was suppressed with KCH exposure, and critical marker (CD14) was identified as the recognition protein to KCH. Using molecular docking, the binding sites of KCH to CD14 were found to have Arg53 and Asp25 amino acids that KCH recognized as regions to inhibit LPS binding. KCH are useful as a new preventive and therapeutic food ingredient for inflammatory diseases.